PELATIHAN PENERAPAN PENGELOLAAN PELAYANAN KEPERAWATAN INPRO DALAM GEDUNG PUSKESMAS BAGI PERAWAT PUSKESMAS KABUPATEN GARUT: Pengabdian Masyarakat - Iwan Wahyudi; Cencen Hendra Setiawan; Tanti Suryawantie; Rudy Alfyansah; Dian Roslan Hidayat; Ishmah Hamidah; Muhammad Ramdan (Jurnal Pengabdian Masyarakat DEDIKASI, 2025)
Nursing services are a form of professional service which is an integral part of health services based on nursing knowledge and tips aimed at individuals, families, groups or communities, both healthy and sick. Several problems related to the implementation of the role of nurses are found in primary health services. The main phenomenon found was a mismatch in implementing the roles and functions of nurses in services at the Community Health Center. This community service activity aims to improve nursing services by strengthening aspects of autonomy, leadership, collaboration and work environment which are integrated into services in the Puskesmas building in a professional manner. The method used is pre and post tests related to the material, then continued with the delivery of the material. The result of this community service is an increase in knowledge before and after the activity. It is hoped that from this community service nurses can provide better nursing services.